A process to improve collaborative work through shared understanding in problem-solving activities - Agredo Delgado, Vanessa (2022)
Collaborative work is becoming increasingly complex and assertive communication is necessary to solve problems in collaborative activities, where the actors must coordinate so that the group works effectively and efficiently. However, achieving true collaboration is not an easy task, there are many factors that influence its achievement, where many of these have been investigated, but the analysis of critical cognitive factors is very scarce, and more those that allow good communication and consequently good coordination. One of them is shared understanding since when working collaboratively there must be common knowledge and understanding, which works as a joint reference base to work effectively and efficiently. Therefore, this work seeks to define a process to improve collaborative work through the construction, monitoring, and assistance of shared understanding. The process has had several versions and each of them has been validated in different contexts, obtaining different types of results, both in terms of its specification and formalization, as well as in terms of its use related to ease of use, feasibility, and usefulness in the construction of shared understanding, which has allowed improving the aspects that have been identified. Through a final validation in a case study, it was determined that the process does improve collaborative work, however, it is still necessary to have technological support elements and it is necessary to lighten the elements that compose it to make it more agile to use.